Моделювання режимів та регулювання частоти обертання вентильно-індукторного двигуна з перетворювачем із С-скиданням коливальним поверненням енергії при зміні кутів комутації - Мазуренко, Леонід Іванович; Бібік, Олена Василівна; Білик, Олександр Анатолійович; Шихненко, Максим Олегович (НТУ "ХПІ", 2016)
Виконано математичне моделювання та проведено експериментальні дослідження статичних режимів при варіюванні напругою живлення та кутами комутації вентильно-індукторного двигуна з перетворювачем із С-скиданням і коливальним поверненням енергії. Визначено коефіцієнт корисної дії, механічні характеристики та діапазон стабілізації частоти обертання вентильно-індукторного двигуна. Проведено порівняльний аналіз результатів математичного моделювання з експериментальними даними.

The aim of the article is development of mathematical model of switched reluctance motor (SRM), researching of working characteristics, comparison of results of numeral calculations of the modes with experimental results and determination of range of stabilizing of rotor speed. Experimental facility of research of modes at varying of rotor speed of experimental model of switched reluctance motor configuration 6/4 on the basis of the induction motor 4AA56A4 (output power 120 W) using a converter with the C-dump and the oscillation return of energy was developed. The mechanical and energetic characteristics of the SRM at different supply voltages of DC link and switch-on angles at the constant zone of commutation (Qk=30°) were defined. A mathematical model of switched reluctance motor was developed. It consist of compositions: inductor machine, converter with the C-dump and the oscillation return of energy, control system by position of rotor, load. Matlab and Simulink are used for simulation. The major losses in the motor and efficiency were evaluated. Adequacy of mathematical model at comparison of results of numeral and experimental researches is appraised. The differences of the expected values of currents of phase and efficiency of motor in the range of switch-on angles 39°- 48° from experimental data does not exceed according to 6...14 % and 2...8 %. The range of stabilizing of rotor speed of experimental model SRM is determinated. So it is possible to provide stabilizing of motor speed at the level of 1500 rpm for voltage 110 V by varying switch-on angles in the range 39°- 48° at the constant zone of commutation.
Simulation mode and speed control of switched reluctance motor using a converter with the C-dump and the oscillation return of energy at changing switching angles
Keywords: вентильно-індукторний двигун; імітаційне моделювання; комутатор; експериментальні дослідження